External skeletal fixation of the tibial shaft fractures - Milenković Saša; Mitković Milorad B.; Radenković Mile (Vojnosanitetski Pregled)
Aim. To present the possibility of a successful use of external skeletal fixation in treating the open and closed tibial shaft fractures with Mitković’s external fixator. Methods. External fixation was used in 115 patients with 118 fresh tibial shaft fractures, 82 males (71.3%) and 33 females (28.7%), average age 43.92 years (16−84). Open tibial shaft fractures were present in 37 (31.36%). All the fractures were treated with Mitković’s external fixator type M 20. Results. The results of external fixation were excellent or good in 94.07% of the cases, and bad in 5.08%. Pin tract infection appeared in 7 (5.93%) patients. In only 3 cases an external fixator was removed and treatment continued with the functional braces. Nonunion occurred in 6 (5.08%) patients, of which 4 were with open fractures (2 Gustilo type IIIB, 1 Gustilo type IIIA, 1 Gustilo type II) and 2 with the segment fractures. Compartment syndrome was observed in 1 (0.85%) patient with closed fracture. Malunion was found in 2 (1.69%) patients. Conclusion. External fixation of tibial shaft fractures is a simple and effective method to enable the safe healing of fractures, early mobilization of the patients, early weight-bearing, as well as early rehabilitation. Fixation of tibial shaft fractures was unilateral with convergent pins orientation, and there was also a possibility of compression and distraction.